HAK PEKERJA DALAM PERJANJIAN KERJA WAKTU TERTENTU DITINJAU DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - I Wayan Partama Putra (Fakultas Hukum Universitas Dwijendra, 2021)
Abstract The process of producing goods and services, workers in this case cannot be released in the role of their duties and functions. Not only is it a very valuable asset and cannot be separated from the ongoing business activities. Companies and workers have a very close relationship. Companies rely on workers for the successful production process. Without the role of these workers, the production process will not be good and will not even be able to run. Therefore, there is a need for legal awareness by business actors in protecting the rights of their workers so as to maintain to increase the productivity and stability of the company. Such protection can be done by providing guidance, recognition of human rights, protection of physical and non-physical and socioeconomic through applicable norms and in accordance with the mandate of the Indonesian Repuplik State Constitution of 1945. This research is a normative legal research, namely by examining library materials by conducting a study of the laws and regulations relating to workers' rights in making work agreements. Law No. 13 2003 concerning Manpower is a legal material that the author uses in obtaining data for research.The conclusion of this research is that a fixed-term work agreement is a job based on the type and period of completion of a job. Every worker in a work agreement for a specified period of time has the right to become an employee with an unspecified time work agreement. Unilateral termination of a work agreement for a specified period of time may result in the provision of compensation. The benefits provided to workers in a work agreement for a specified period of time must be in accordance with statutory regulations.